Body image and its relationship to the formation of psychological attitudes towards physical activity and sports among secondary school students (a field study in a secondary school in Algeria) - hechaichi, abdeouahab (sports creativity, 2025)
The main purpose of the present study was to detect the relationship between body Image (bodily self) and attitudes toward physical activity and sport for high school females and males students. The sample of this study contained 80 students (40 males, 40 females), which selected randomly from the third class in high school, then have been applied on the participants the bodily self scale, and the Kenyon. G, Attitudes toward physical activity and sport scale. The results of the study revealed significant sex differences in bodily self, between high school students, while there aren't sex differences in attitudes toward physical activity and sport for high school females and males students, accept in achievement sport physical activity experience, for students with high attitudes, as well as the relationship between bodily self and attitudes toward physical activity and sport, for high school females and males students, were not detected, accept in fitness and esthetic physical